2019
DOI: 10.3892/etm.2019.8356
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑496 suppresses tumor cell proliferation by targeting BDNF in osteosarcoma

Abstract: MicroRNAs (miRNAs) are integrally involved in biological and pathobiological development. Many studies have demonstrated the abnormal expression of microRNA-496 (miR-496) in various human malignant tumors. The present study was designed to investigate the functions and the underlying mechanisms of miR-496 in osteosarcoma (OS) progression. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to determine the expression of miR-496 in OS tissues and cell lines. Luciferase activity was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…50 An earlier study showed that Bdnf mRNA can be targeted by miR-496a-3p. 51 Our data showed that removal of TRAX caused an elevation of miR-496a-3p and a reduction in Bdnf (Fig. 2F,G), indicating that miR-496a-3p is a substrate of the TRAX/Translin complex, which negatively regulates the expression of Bdnf.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…50 An earlier study showed that Bdnf mRNA can be targeted by miR-496a-3p. 51 Our data showed that removal of TRAX caused an elevation of miR-496a-3p and a reduction in Bdnf (Fig. 2F,G), indicating that miR-496a-3p is a substrate of the TRAX/Translin complex, which negatively regulates the expression of Bdnf.…”
Section: Discussionmentioning
confidence: 58%
“…[44][45][46][47] Levels of these four miRNAs and their corresponding target mRNAs that have previously been implicated in either HD or/and neurons were validated using qRT-PCR assays (Table 1; Supplementary Appendix S1). [44][45][46][47][48][49][50][51][52][53] The detailed rationale underlying the selection of target miRNAs for validation is described in the Materials and Methods section of the Supplementary Appendix S3. TRAX ablation elevated all four miRNAs in the context of HD mice.…”
Section: Trax Regulated the Mirna-mrna Axis In Hdmentioning
confidence: 99%
“…The present study revealed that NNT-AS1 acted as a sponge of miR-496, which acted as a tumor suppressor in CRC cells. Previous studies have suggested that miR-496 functions as a tumor suppressor in various cancers, such as CRC, lung cancer and osteosarcoma (18,39,40). A recent study identified that miR-496 acted as an oncogene and promoted malignancy in CRC cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal proliferation is a unique feature of tumor cells andthe inhibition of tumor cell proliferation is controversial (23). miRNA serves an important role in tumorigenesis and the development of malignant tumors and regulates the proliferation and invasion of tumor cells by combining with target genes (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%